Hadith #2912 - Sahih Muslim - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن (Sahih Muslim)
By Him In Whose Hand is my life; the rest of the hadith is the same.
Grade: Sahih

Hadith #3823 - Sahih Muslim - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن (Sahih Muslim)
I asked Rafi’ b. Khadij about the renting of land for gold and silver, whereupon he said: There is no harm in it for the people let out land situated near canals and at the ends of the streamlets or portion of fields. (But it so happened) that at times this was destroyed and that was saved. whereas (on other occasions) this portion was saved and the other was destroyed and thus no rent was payable to the people (who let out lands) but for this one (which was saved). It was due to this that he
Grade: Sahih

Hadith #3824 - Sahih Muslim - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن (Sahih Muslim)
We were the major agriculturists of the Ansar and so we let out land (saying): The produce of this (part of land) would be ours and (the produce) of that would be theirs. But it so happened that at times this (land) gave harvest, but the other one produced nothing. So he (the Holy Prophet) forbade this. But so far as the payment in silver (dirham, a coin) is concerned, he did not forbid.
Grade: Sahih

Hadith #6796 - Sahih Muslim - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن (Sahih Muslim)
We were in the company of Allah’s Messenger (ﷺ) and he delivered to us a sermon and made a mention of Hell-Fire. Then I came to my house and began to laugh with my children and sport with my wife. (Hanzala) further reported: I went out and met Abu Bakr and made a mention of that to him. Thereupon he said: I have done the same as you have mentioned. So we went to see Allah’s Messenger (ﷺ) and said to him: Allah’s Messenger, Hanzala has turned to he a hypocrite. And he (the Holy Prophet)
Grade: Sahih

Hadith #12 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“The deeds connected to the Fitrah are: Clipping the nails, removing the mustache and shaving the pubes.”
Grade:

Hadith #424 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan al-Nasa'i)
“When the Messenger of Allah (ﷺ0 performed Ghusl from Janabah, he would wash his hands, then perform Wudu’ as for prayer, then run his fingers through his hair until he was sure the water had reached the scalp, then he would pour water over his head three times, then wash the rest of his body.”
Grade:

Hadith #2520 - Sunan al-Nasa'i - Ahmed bin Suliaman أحمد بن سليمان; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“Give Zakah of your fast.” The people started looking at one another. So he said: “Whoever is here of the people of Al-Madinah, get up and teach your brothers, for they do not know that the Messenger of Allah has enjoined Salaqatul Fitr upon young and old, free and slave, male and female; half a Sa’ of wheat or a Sa’ of dates or barely.” Al_Hasan said: ‘If Allah has given you more, then give more generously of wheat or something else.”‘
Grade:

Hadith #2923 - Sunan al-Nasa'i - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“I head Ibn Abbas sya: ‘Usmah bin Zaid told me that the Prophet entered the YHouse, and supplicated in all its corner, but he did not pray inside unitl he came out; when he came out he prayed two Rakahs in front of the Kabah.'”
Grade:

Hadith #2938 - Sunan al-Nasa'i - al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Amr bin 'Uthman عمرو بن عثمان بن عفان; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن (Sunan al-Nasa'i)
“This is what I saw the Messenger of Allah doing.”
Grade:

Hadith #3558 - Sunan al-Nasa'i - al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Yusuf bin 'Isa bin Dinar يوسف بن عيسى بن دينار الزهري (Sunan al-Nasa'i)
“Go out and take the harvest of your date palms, for perhaps you will give Zakah or do some good (give voluntary charity).”
Grade:

Hadith #3705 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; Hiban bin Hilal حبان بن هلال; Muhammad bin Hatim Al-Samayn محمد بن حاتم البغدادي - السمين; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“The one who takes back his gift is like the one who goes back to his vomit.”
Grade:

Hadith #3714 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; Hiban bin Hilal حبان بن هلال; Muhammad bin Hatim Al-Samayn محمد بن حاتم البغدادي - السمين; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“My father narrated to us: Ubaidullah -he is, Ibn ‘Amr- narrated to us, from Sufyan, from Ibn Abi Najih, from Tawus, from Zaid bin Thabit, that the Prophet said: ‘Ar-Ruqba is permissible.'”
Grade:

Hadith #4284 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Swyd bin Nsr bin Swyd سويد بن نصر بن سويد (Sunan al-Nasa'i)
“I asked the Messenger of Allah about hunting with the Mirad. He said: ‘whatever is struck with the sharp edge, eat, and whatever is hit with its broad side, it is an animal killed by a blow. “” He said: “And I asked him about hunting dogs. He said: ‘If you release your dog and mention the name of Allah over it, then eat.,’ I said: ‘Even it he kills it?’ He said: ‘Even if he kills it?” He said: ‘Even if he kills it. But if he has eaten some of it, then do not eat. And if
Grade:

Hadith #4522 - Sunan al-Nasa'i - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“The messenger of Allah forbade two kinds of transactions: Mulamash and Mumabadha.”
Grade:

Hadith #4594 - Sunan al-Nasa'i - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sufyan bin 'Uyaynah سفيان بن عيينة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
he did not like to exchange Dinars for Dirhams or Dirhams for Dinars.
Grade:

Hadith #4906 - Sunan al-Nasa'i - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“A thief was brought to the hand.” They said: “We did not think that you would take it so far.” He said: “If it were Fatimah (who stole), I would cut off her hand.”
Grade:

Hadith #4907 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Yonus bin 'Abdul A'la al-Sadfi يونس بن عبد الأعلى بن ميسرة الصدفي (Sunan al-Nasa'i)
a woman stole at the time of Messenger of Allah and they said: “We cannot speak to him concerning her; there is no one who can speak to him except his beloved, Usamah.” So he spoke to him, and he said”O Usamah, the Children of Israel were destroyed for such a thing. Whenever a noble person among them stole, they would let him go, but if a low-class person among them stole, they would cut off his hand. If it were Fatimah bint Muhammad (who stole), I would cut off her hand.”
Grade:

Hadith #5001 - Sunan al-Nasa'i - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Ikrama bin Khalid bin al-Aas عكرمة بن خالد بن العاص بن هشام; Muhammad bin 'Abdullah bin 'Ammar محمد بن عبد الله بن عمار (Sunan al-Nasa'i)
“The Prophet said: ‘I give to some men, and leave those who are dearer to me, without giving them anything, lest (the former) be thrown into Hell on their faces.'”
Grade:

Hadith #5299 - Sunan al-Nasa'i - Abdullah bin al-Harith bin 'Abdul Malik عبد الله بن الحارث بن عبد الملك; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan al-Nasa'i)
The Messenger of Allah had a ring made of gold and he used to wear it with the stone (Fass) against his palm, and the people did likewise. Then he sat on the Minbar and said: “I used to wear this ring and put its stone (Fass) on the inside.” Then he threw it away and said: “By Allah, I will never wear it again.” And the people threw their rings away.
Grade:

Hadith #3339 - Sunan Abi Dawud - Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس; Uthman bin Muhammad (Sunan Abi Dawud)
The memory of Sufyan was stronger than mine.
Grade: Sahih

Hadith #1399 - Sunan Ibn Majah - Abdur Rahman bin 'Abdullah bin Sabit عبد الرحمن بن عبد الله بن سابط; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hanzala bin Abi Sufyan bin 'Abdur Rahman حنظلة بن أبي سفيان بن عبد الرحمن (Sunan Ibn Majah)
“It is not an act of righteousness to fast while traveling.”
Grade: